Anti-SRP Immune-Mediated Necrotizing Myopathy and Recent Cytomegalovirus Infection: A Case Report - Sampaio, Beatriz; Gomes, Felisbela; Teixeira, João; Leal, Mafalda; Rebelo, Maria (International Journal of Innovative Research in Medical Science, 2025)
Anti-signal recognition particle immune-mediated necrotizing myopathy (IMNM-SRP) is a rare, severe form of idiopathic inflammatory myopathy (IIM), marked by proximal muscle weakness, elevated creatine kinase levels, and significant muscle necrosis. This case report describes a 73-year-old woman with IMNM-SRP following a recent cytomegalovirus (CMV) infection, who presented with progressive proximal muscle weakness, dyspnea and dysphagia. Despite the initial severity, the patient showed substantial clinical improvement with an intensive immunosuppressive regimen, including corticosteroids, intravenous immunoglobulin, rituximab, and plasmapheresis. This case highlights the possibility of CMV as a triggering factor for IMNM-SRP, a rare association in current literature. The report emphasizes the role of early recognition and aggressive treatment in optimizing outcomes in immune-mediated necrotizing myopathies and underscores the need for further research into viral infections as potential contributors to its pathogenesis.